Los intereses de la política exterior sueca: socialdemocracia y liberalismo - Salcido Zugasti, Jorge E. (Revista Mexicana de Política Exterior, 2022)
Sweden currently ranks among the world’s most highly developed countries in political, social, economic and technological terms. Far from being a coincidence, this is the result of a wellthought-out government strategy. Differing views on foreign policy within the country’s political parties, from the socialists to the center-right, tend to be approach-related as opposed to ideological, and this has facilitated the successful opening-up of the country to new political and economic ideas. After summarizing the main aspects of Sweden’s foreign policy, the author notes that, rather than change, what is required are measures that provide continuity and coherence to the country’s efforts to find its footing on the international arena, measures that transcend party interests and differences. The main virtue of Sweden’s political and economical development model, concludes Salcido, has been consistency and a long-term vision in the planning and implementation of government programs. Political and economic liberalization have taken place gradually, while the legal and institutional guarantees that safeguard national, public and private interests have been upheld. Over and beyond ideological differences and political interests, Sweden has managed to give continuity to a development model and a nation-building project that effectively combines the advantages of a market economy with the socialist principle of equal opportunities and the freedoms of a democracy. Indubitably, there is much to be learned from the Swedish model. Given the crisis the global economy is currently facing, perhaps the time has come to rethink the benefits of a regulated capitalism geared toward social wellbeing.